Are Systematic Screening for Vitamin D Deficiency and Vitamin D Supplementation Currently Feasible for Ankylosing Spondylitis Patients? - Mickael Essouma; Jean Jacques N. Noubiap (International Journal of Inflammation)
Beyond its role in calcium and phosphorus metabolism for healthy bone mineralization, there is increasing awareness for vitamin D contribution in modulation of immune reactions. Given that ankylosing spondylitis (AS) is a chronic inflammatory disease involving excess immune/inflammatory activity and posing great therapeutic challenges, it is conceivable to claim that vitamin D treatment may be a safe and effective treatment to influence or modify the primary disease and its related comorbidities. Nevertheless, consistent body of research supporting this hypothesis is still lacking. In this paper, we examine whether systematic screening and treatment for vitamin D deficiency are feasible at present. We will review the immunomodulatory role of vitamin D and its contribution in initiation and progression of AS, as well as how they would determine the occurrence of comorbid conditions. Our conclusion is that despite the overwhelmed interest about vitamin D treatment in AS patients, systematic screening and treatment for vitamin D deficiency of all AS patients are not feasible as yet. This stresses the need for further extensive well-designed research to prove vitamin D efficacy in AS beyond bone protection. And if utility is proven, personalized treatment regimes, duration of treatment, and threshold values for vitamin D should be provided.